Comparación De Procedimientos Y Resultados Obtenidos Del Uso De Vacunas Contra Las Garrapatas - Barrera Reita, Cindy Jyneth; Rodriguez Huteras, Angie Meliza (Universidad Antonio Nariño, 2024)
Tick ​​infestations in bovine production over the years continue to be a major problem in this sector due to the great economic losses by reducing the weight of the animals and, however, in dairy production, due to the high resistance that has been generated. to a range of methods implemented for the limitation of these